2018
DOI: 10.1371/journal.pcbi.1005943
|View full text |Cite
|
Sign up to set email alerts
|

Identification of allosteric inhibitors of the ecto-5'-nucleotidase (CD73) targeting the dimer interface

Abstract: The ecto-5’-nucleotidase CD73 plays an important role in the production of immune-suppressive adenosine in tumor micro-environment, and has become a validated drug target in oncology. Indeed, the anticancer immune response involves extracellular ATP to block cell proliferation through T-cell activation. However, in the tumor micro-environment, two extracellular membrane-bound enzymes (CD39 and CD73) are overexpressed and hydrolyze efficiently ATP into AMP then further into immune-suppressive adenosine. To circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…One caveat of the in vitro study was that APCP is a competitive inhibitor. Its efficiency and metabolic stability are lower when the concentration of substrate is high compared to allosteric inhibitors 42 . However, we demonstrated that blocking of CD73 by APCP had significant effect on cellular behavior and EMT progression in TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…One caveat of the in vitro study was that APCP is a competitive inhibitor. Its efficiency and metabolic stability are lower when the concentration of substrate is high compared to allosteric inhibitors 42 . However, we demonstrated that blocking of CD73 by APCP had significant effect on cellular behavior and EMT progression in TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its key role in purinergic signaling pathways regulation, ecto -5′-NT has been recognized as a promising biological target for multiple diseases and pathophysiological events, including cancer, autoimmune diseases, inflammation, infections and ischemia-reperfusion injury. The remarkable efforts that have been made by scientific community towards discovery of novel ecto -5′-NT inhibitors can be attested by the numerous studies that account for potential bioactive compounds and/or drug candidates targeting this enzyme [ 42 , 43 , 44 , 45 , 46 , 47 , 49 , 59 ]. Despite the encouraging results obtained by most of them, controls for inhibitors aggregation and/or precipitation have not been systematically reported so far.…”
Section: Resultsmentioning
confidence: 99%
“…Considering its importance for therapy, the screening for ecto -5′-NT inhibitors has become urgent. Although numerous studies describing ecto -5′-NT inhibitors have been published in the literature [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], the corresponding procedures and controls concerning compound aggregation have not been systematically described so far for this target enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…[51] 5′-Nucleotidases can be found either membrane bound (ecto-5′−-nucleotidase/CD73) or in soluble form in the cells. [57] However in the present study we have tested our polyphenols only on CD73 (ecto-5′-nucleotidase) activity since high cellular ATP concentrations deactivates soluble 5′-nucleotidase function. [58] The only flavonol that inhibited CD73 activity in intact HUVECs was quercetin, and the inhibition was only partial and requiring relatively high quercetin concentrations (50 m).…”
Section: Discussionmentioning
confidence: 99%